Brand love matters to Millennials: the relevance of mystery, sensuality and intimacy to neo-luxury brands. Issue 7 (6th June 2019) - Rodrigues, Clarinda; Rodrigues, Paula
Abstract : Purpose: This paper aims to investigate the mediating effect of brand love on purchase intention and word-of-mouth through mystery, sensuality and intimacy as brand image dimensions in the context of neo-luxury brands. It also explores the moderating effect of duration and intensity of consumer-brand relationships on brand image dimensions. Design/methodology/approach: The data collection was done via an online survey of a representative group of Millennials. Data analysis was performed using structural equation modeling and multi-group analysis. Findings: The paper suggests that brand love mediates the relationship between brand image, purchase intention and word-of-mouth for both Apple and Michael Kors brands. This study also identifies differences in the effects of intimacy, sensuality and mystery on brand love. Additionally, it is demonstrated that the moderation effect of intensity and duration of consumer-brand relationships varies among the two neo-luxury brands. Research limitations/implications: Further research should aim at investigating other categories of products and services in the field of neo-luxury, as this study focus on fashion and mobile brands. Other antecedents and outcomes of brand love should also be evaluated, as well as other moderating variables. Originality/value: This paper contributes to the fast-growing consumer-brand relationships literature by exploring the role of brand love in the context of the emergent neo-luxury paradigm. It also intends to provide a better understanding of how to build and nurture an effective brand image through a multidisciplinary approach that combines mystery, sensuality and intimacy.